Physiotherapy Management of Low Back Pain in Indonesian Para Badminton Athlete: a Case Study - Rezky Guna Putra; Suryo Saputra Perdana; Amalia Nur Azizah (Kinestetik : Jurnal Ilmiah Pendidikan Jasmani, 2023)
This study aims to determine the role of physiotherapy in the management of low back pain case in Indonesian para badminton athlete. The research method used in this research is a descriptive case study. The sample in this study is Mrs. R, aged 30, who is a professional para badminton athlete. The main complaints were pain and limited range of motion. Assessments were carried out using VDS for pain, Schobers test for ROM and ODI for functional activity ability. The physiotherapy interventions used were US, TENS, and William Flexion Exercise. The research procedure was that the researchers conducted examinations and measurements including physical examinations, specific examinations, and examination of functional activity ability. The researchers provided US, TENS, and William Flexion Exercise interventions, and then the researchers evaluated and processed data. After 6 therapy sessions at the NPC Indonesia clinic, pain assessment showed a decrease in silent pain from T1 score 1 to 0 in T6, in compression pain from T1 score 3 to T6 score 1, and in motion pain from T1 score 5 to T6 score 2. Evaluation of range of motion showed an increase in range of motion in trunk flexion from therapy 1 value of 5 cm to therapy 6 value 8 cm. In trunk extension movements from therapy 1 value of 7 cm to therapy 6 value  9 cm. Evaluation of functional activity showed an increase in functional activity from T1 with a total of 25 indicating severe disability to T6 with a total of 9 indicating mild disability.